Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006731
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies: effects of financial incentives for prescribers

Abstract: Based on the evidence in this review from three Western European countries, drug budgets for physicians in private practice can limit drug expenditure by limiting the volume of prescribed drugs, increasing the use of generic drugs or both. Since the majority of studies included were found to have serious limitations, these results should be interpreted with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 82 publications
3
64
0
2
Order By: Relevance
“…Using three recent reviews on pricing and purchasing policies, financial incentives for prescribers and co-payment and co-payment caps, the challenges and lessons for such reviews and future research are outlined. [3][4][5] The approach…”
Section: Box 31 Case Study: Heterogeneity Of Methods and Findings Inmentioning
confidence: 99%
“…Using three recent reviews on pricing and purchasing policies, financial incentives for prescribers and co-payment and co-payment caps, the challenges and lessons for such reviews and future research are outlined. [3][4][5] The approach…”
Section: Box 31 Case Study: Heterogeneity Of Methods and Findings Inmentioning
confidence: 99%
“…31,32,33,34 Other reviews of the literature and issues -some of which were published after the overview of reviews 35,1,36,37,3,38,39 -are also relevant. The four reviews included were rated "moderate" in quality and included 32 different evaluations of financial incentives.…”
Section: Summary Of Conclusion Of Other Systematic Reviewsmentioning
confidence: 99%
“…Financial incentives have previously been shown to influence on the uptake of new drugs (149,150). A recent review showed that the mere presence of financial incentives may influence prescriptions (151). Based on 13 studies, this review concluded that when a group of physicians, or individual physicians, manage their own budget, they prescribe fewer and less expensive drugs.…”
Section: Outer Settingmentioning
confidence: 99%